GAMBARAN PENGETAHUAN KADER KESEHATAN MENGENAI GIZI IBU HAMIL - ratih indraswari (Universitas Airlangga, 2018)
Abstract: Maternal Mortality Rate (MMR) is still a serious concern of the government. Various efforts have been made to reduce the number in all regions in Indonesia. Village health cadres have an important role in delivering health information and monitoring the health of pregnant women. Maternal health problems are often caused by maternal feeding behaviors that are incompatible with the Balanced Nutrition Guidelines. This study aimed to find out the knowledge of cadres about nutrition of pregnant women. The research method used cross-sectional with quantitative approach and total population sample technique. The sample in this research is 30 health cadres in Pucakwangi Village, Pati Regency, Central Java. The results showed that most cadres knew the definition of nutrition as a substance contained in food (80%). As many as 50% of respondents knew the nutritional function for growth, 10% of cadres did not know that exclusive breastfeeding is only for infants aged 0-6 months, 23.3% did not know about the provision of Fe tablets to pregnant women. Only 33.3% of cadres knew that carbohydrates and minerals are nutrients. In addition, only 80% of cadres knew that basic food needs to be consumed daily. Less than half of cadres who know that milk (26.7%) and nuts (30%) are a source of protein. Knowledge of health cadres on the nutrition of pregnant women still needs to be improved, especially regarding the source of nutrition in food and the provision of Fe tablets. Keywords: Knowledge, nutrition, pregnant women, cadre.     Abstrak: Angka Kematian Ibu (AKI) masih menjadi perhatian serius pemerintah. Berbagai upaya telah dilakukan untuk menekan tingginya AKI di seluruh wilayah di Indonesia. Kader kesehatan di tingkat desa memiliki peran penting dalam menyampaikan informasi kesehatan dan memantau kesehatan ibu hamil. Masalah kesehatan ibu seringkali disebabkan oleh perilaku makan ibu yang tidak sesuai dengan Pedoman Gizi Seimbang. Penelitian ini bertujuan untuk mencari tahu gambaran pengetahuan kader mengenai gizi ibu hamil. Metode penelitian menggunakan metode cross-sectional dengan pendekatan kuantitatif dan teknik sampel total populasi. Sampel dalam penelitian ini adalah 30 kader kesehatan di Desa Pucakwangi Kabupaten Pati Jawa Tengah. Hasil penelitian menunjukkan bahwa sebagian besar kader mengetahui pengertian gizi sebagai zat yang terkandung dalam makanan (80%). Sebanyak 50% responden mengetahui fungsi gizi untuk pertumbuhan, 10% kader tidak tahu bahwa ASI eksklusif adalah pemberian ASI saja untuk bayi usia 0-6 bulan, 23,3% tidak tahu mengenai pemberian tablet Fe kepada ibu hamil. Hanya 33,3% kader yang mengetahui bahwa karbohidrat dan mineral merupakan zat gizi. Selain itu, hanya 80% kader yang mengetahui bahwa makanan pokok perlu dikonsumsi setiap hari. Kurang dari separuh kader yang mengetahui bahwa susu (26,7%) dan kacang-kacangan (30%) merupakan sumber protein. Pengetahuan kader kesehatan mengenai gizi ibu hamil masih perlu ditingkatkan, khususnya mengenai sumber gizi dalam makanan dan pemberian tablet Fe.   Kata Kunci: Pengetahuan, gizi, ibu hamil, kader.